Case studies in cell biology - Casem, Merri Lynn (Problem sets in biological and biomedical sciences., 2016)
"Case Studies in Cell Biology presents real world scenarios to help readers use science process and reasoning skills. The case studies require application and analyzation of concepts beyond rote memory of biological concepts. The book is based on the student learning outcomes from the American Society for Cell Biology, offering practical application for both the classroom and research laboratory. Guides the reader in applying knowledge directly to real world scenarios Includes case studies to bridge foundational cell biological concepts to translational science Aids students in synthesizing information and applying science processes."